El Uso de las TIC en la Educación Superior: Aplicación a los Docentes de la Unidad de Admisión y Nivelación de la Escuela Superior Politécnica de Chimborazo - Germán Torres; Marco Salazar; Gabriel Pilaguano; Gabriela Fonseca (European Scientific Journal, ESJ, 2019)
The paper focuses on the use of ICT in higher education using a case study of teachers of the Admission and Leveling Unit at the Polytechnic School of Chimborazo. A virtual platform was used in the course of their academic activities which allow them to have a clear idea of what type of information circulates through the said platform. This study generates tools that allow students and teachers of the Admission and Leveling Unit of the Higher Polytechnic School of Chimborazo to have an effective communication. The methodology used in this study is a system that collects information from a selected group of people. It also allows them to collect primary data from the respondents. The application of the field technique and the survey technique shows that 63.4% of teachers use their virtual classrooms as a support tool in their academic activities. 61% of teachers monitor access to the resources they publish and are used by their students in virtual classrooms at ESPOCH. The universalization of the use of ICT is evident since in Ecuador, according to data from the Ministry of Telecommunications, 91% of the population between 14 - 50 years make use of these communication tools daily through their smart devices. Therefore, thisstudy is aimed at raising the awareness of the teachers of the Admission and Leveling Unit of the ESPOCH on the use of the Platform. 97.6% of teachers indicate that the use of ICT can improve the teaching process through the use of the virtual classroom. Guidelines are also established to improve communication outside the classroom to students with academic purposes, transmitting quality information through the virtual classrooms where the teacher becomes the tutor of the subjects taught in the Unit. Admission of the ESPOCH, thus, guarantees immediate response methods from the teacher to the student and vice versa.El presente trabajo permite establecer el uso que los docentes de la Unidad de Admisión y Nivelación de la Escuela Superior Politécnica de Chimborazo, le dan a la plataforma virtual en sus actividades académicas permitiendo tener una idea clara de qué tipo de información circula a través de dicha plataforma. Este estudio genera herramientas que permiten que los estudiantes y docentes de la Unidad de Admisión y Nivelación de la Escuela Superior Politécnica de Chimborazo UAN tengan una comunicación efectiva. La metodología utilizada es la sistemática que recolecta información de un grupo seleccionado de personas, la misma que nos permite recopilar datos primarios de los encuestados. Se obtiene como resultado de la aplicación de la técnica de campo y la encuesta que el 63,4% de los docentes utilizan sus aulas virtuales como herramienta de apoyo en sus actividades académicos, que el 61 % de los docentes realiza un seguimiento al acceso de los recursos que publican y los cuales son utilizados por sus estudiantes en las aulas virtuales en la ESPOCH. La universalización de la utilización de las TICs es evidente, ya que en el Ecuador, según datos del Ministerio de Telecomunicaciones, un 91% de la población entre 14 y50 años hace uso diariamente de dichas herramientas de comunicación a través de sus dispositivos inteligentes. Por tal motivo, con este estudio se pretende concientizar a los docentes de la Unidad de Admisión y Nivelación de la ESPOCH sobre el uso de la Plataforma, 97,6% de los docentes indican que el uso de las TIC puede mejorar el proceso de enseñanza con el uso del aula virtual. También se establece lineamientos para mejorar la comunicación fuera del aula de clase hacia los estudiantes con fines académicos, transmitiendo por medio de las aulas virtuales información de calidad en donde el docente se convierta en el tutor guía de las asignaturas que se imparten en la Unidad de Admisión de la ESPOCH, garantizando así métodos de respuesta inmediata desde el docente hacia el estudiante y vice versa